The Development of Interactive E-book of Teaching Indonesian for Speaker of Other Language (TISOL) Containing Local Wisdom with Scientific-Thematic Approach. (July 2020) - Saddhono, K; Ridwan, M; Suherman, A; Anwar, K; Putri, N Q H
Abstract: TISOL learning definitely needs to notice planning, processes, evaluations, learning materials, media, and methods used. However, selecting the media and learning material should give foreign students the description about Indonesia condition so that can lead them to be more interested in learning Indonesian language. This study was a developmental research aiming to apply a model of the local wisdom-based interactive book for TISOL students in Indonesia. The research stages are applied 4 stages, namely (1) preliminary study or exploration, (2) prototype development, (3) prototype test, and (4) dissemination or product implementation. The location of this study was institutions which organizing TISOL in Indonesia. This study was planned to be conducted in 3 years to get data as a reference for the product development and implementation in term of the interactive e-book. Sources of data were (1) TISOL students, instructors, organizers and persons in charge; (2) TISOL teaching-learning activities in TISOL institution; (3) data which obtained through questionnaire containing questions to emphasize the result of the exploration, and (4) textbooks used by BIPA institutions and also learning curricula. After passing some assessment, such as expert assessment, small-scale and wide-scale tests, and experiment class test, interactive e-book for TISOL learning conducted in high level score. Therefore, it can be said that the use of TISOL interactive e-book on learning process as a variation in giving learning materials in TISOL. It can be also considered as an input for TISOL learning developers to give innovation on their products developed.